Stress Analysis of a Maxillary Central Incisor Restored with Different Posts - Adanir, Necdet; Belli, Sema (European Journal of Dentistry, 2007)
Objectives: To evaluate the effects of different post materials on the stress distribution in an endodontically treated maxillary incisor.Materials and Methods: A pseudo 3-dimensional finite element model was created in a labiolingual cross-sectional view of a maxillary central incisor and modified according to five posts with different physical properties consisting stainless steel, titanium, gold alloy, glass fiber (Snowpost), and carbon fiber (Composipost). A 200 N force was then applied from two different directions; a) vertical load on the incisal edge, b) 45 degree diagonal load above the cingulum location. Stress distribution and values were then calculated by considering the pseudo three dimensional von Mises stress criteria.Results: Under two loading conditions, post made of steel showed greatest stress concentration at the post/dentin interface followed by titanium, gold alloy, Snowpost and Composipost. However, Composipost, which elastic modulus was closer to the dentin, produced highest stress values at 1/3 cervical area.Conclusions: Within the limitation of this simulated mechanical analysis, we can conclude that the physical characteristics of posts were important on stress distributions in post and core applications. Glass fiber post revealed more balanced stress distribution under functional forces. (Eur J Dent 2007;2:67-71)
Keywords: Stress analysis; Finite element method; Endodontically treated teeth; Fiber post; Metal post